2017
DOI: 10.3389/fmicb.2017.00705
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of the RNA-Dependent RNA Polymerase and Capsid Genes of Human Norovirus Genotype GII.2 in Japan during 2004–2015

Abstract: The RNA-dependent RNA polymerase (RdRp) and capsid (VP1) genes of 51 GII.2 human norovirus (HuNoV) strains collected during the period of 2004–2015 in Japan were analyzed. Full-length analyses of the genes were performed using next-generation sequencing. Based on the gene sequences, we constructed the time-scale evolutionary trees by Bayesian Markov chain Monte Carlo methods. Time-scale phylogenies showed that the RdRp and VP1 genes evolved uniquely and independently. Four genotypes of GII.2 (major types: GII.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 8 publications
3
27
0
Order By: Relevance
“…We found that the rate of the HuNoV VP1 gene in GII.2 strains, including 2016 strains was 3.26 × 10 -3 substitutions/site/year. However, previous studies showed different evolutionary rates ( Eden et al, 2014 ; Kobayashi et al, 2016 ; Mizukoshi et al, 2017 ). For example, Kobayashi et al (2016) suggested it was around 3.76 × 10 -3 substitutions/site/year for the VP1 gene of all HuNoV GII.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We found that the rate of the HuNoV VP1 gene in GII.2 strains, including 2016 strains was 3.26 × 10 -3 substitutions/site/year. However, previous studies showed different evolutionary rates ( Eden et al, 2014 ; Kobayashi et al, 2016 ; Mizukoshi et al, 2017 ). For example, Kobayashi et al (2016) suggested it was around 3.76 × 10 -3 substitutions/site/year for the VP1 gene of all HuNoV GII.…”
Section: Discussionmentioning
confidence: 90%
“…Our main findings are as follows. (1) A common ancestor of the VP1 gene of the 2016 strains diverged from another GII.P16-GII.2 strain around 10 years ago with an evolutionary rate as described ( Mizukoshi et al, 2017 ) ( Figure 1 ). (2) A common ancestor of the RdRp region of the 2016 strains diverged from the RdRp region of the GII.P16-GII.4 rather than the previous GII.P16-GII.2 strains in 1999 with a rapid evolutionary rate (around 10 -3 substitutions/site/year) ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Next, we estimated the HuNoV GII.4 VP1 gene evolutionary rate as 7.68 × 10 −3 substitutions/site/year. Our observations are generally consistent with previous observations overall, with GII.4 having a higher evolutionary rate than other genotypes such as GII.7 (2.3 × 10 −3 substitutions/site/year), GII.3 (4.16 × 10 −3 substitutions/site/year), and GII.2 (1.31 × 10 −3 substitutions/site/year) (Bok et al, 2009 ; Bull et al, 2010 ; Siebenga et al, 2010 ; Boon et al, 2011 ; Fioretti et al, 2014 ; Qiao et al, 2016 ; Mizukoshi et al, 2017 ; Parra et al, 2017 ). In addition, we estimated the different evolutionary rates among GII.4 variants.…”
Section: Discussionmentioning
confidence: 99%
“…The values obtained by dividing the numbers of chain lengths by that of the log parameters were used as sample sizes. For the phylogenetic distance analyses, we acquired 3–11,440 data that exhibited the number of all combinations between GII.4 strains included in the dataset (Mizukoshi et al, 2017 ). Detailed statistical data are shown in Tables S2 – S4 .…”
Section: Methodsmentioning
confidence: 99%
“…In our study, GII.P16 was detected with the GII.3 capsid genotype circulating in 2015; however, it was grouped in a different cluster than our GII.P16-GII.4 Sydney strains and previous strains detected in AGE outbreaks in Southern Brazil between 2010 and 2011 [ 10 ]. Recently, GII.P16 re-emerged combined with GII.2 grouped in the same cluster as the polymerase GII.P16 of the new recombinant GII.P16-GII.4 Sydney, differing from the previous one and suggesting the importance of the current GII.P16 polymerase in norovirus circulation worldwide [ 18 , 19 , 47 , 48 , 49 , 50 , 51 , 52 ]. The authors also described the importance of the polymerase for viral fitness and variability [ 19 ]; therefore, the newly acquired polymerase could play a role in the success of this recombinant form.…”
Section: Discussionmentioning
confidence: 99%